Motor Coordination: studying tracking in 6 to 10-year-old children in the Azores Autonomous Region, Portugal - Rui Manuel Garganta da Silva; José António Ribeiro Maia; Vítor Pires Lopes; André F. Teixeira e Seabra; Alcibíades Bustamante; Renata K. Batista Coelho Deus (Universidade Federal de Santa Catarina, 2008)
Azores aged 6 to 10 years of age of both genders; and to estimate the stability of intra-individual changes in inter-individual differences over 4 years. The sample comprised 285 children (143 boys and 142 girls) from the mixed-longitudinal study of the Azores Autonomous Region. Motor coordination was assessed with the KTK test battery which comprises 4 tests: Backward balance, Jumping sideways, Hopping on one leg and Shifting platforms. Basic descriptive statistics, ANOVA II, and auto-correlations were calculated in SPSS 15. We used the of Foulkes and Davies to verify the proportion of children who maintained the same relative position. This calculation was performed using the software LDA. We found increases in mean values, in both genders, across the ages. ANOVA II showed significant differences in all tests over the 4 years, and a significant interaction between time and sex was only observed for the Backward balance. Auto-correlations presented moderate stability. Neither gender exhibited tracking in their performance in the Backward balance and the boys failed to do so in Hopping either, which demonstrates a strong heterogeneity in Motor Coordination development over the 4 years. These results show that children differ substantially along their motor development and calls for a clear understanding of its meaning in educational and didactic terms. Resumo O objetivo do estudo foi caracterizar o desenvolvimento coordenativo em crianças açorianas dos 6 aos 10 anos em função do sexo e estimar a estabilidade da mudança intra-individual nas diferenças inter-individuais ao longo dos quatro anos. A amostra de 285 crianças (143 meninos e 142 meninas) é proveniente do estudo longitudinal-misto da Região Autônoma dos Açores. A coordenação motora foi determinada com a bateria de testes KTK que compreende 4 provas: Equilíbrio à retaguarda, Saltos laterais, Saltos monopedais e Transposição lateral. As estatísticas descritivas básicas, a ANOVA II, assim como as auto-correlações foram calculados no SPSS 15. Recorremos ao de Foulkes e Davies para verificar a quantidade de crianças que mantêm a mesma posição relativa. Este cálculo foi realizado no software LDA. As medidas descritivas básicas revelaram um incremento das médias, em ambos os sexos, ao longo da idade. A ANOVA II mostrou diferenças significativas em todos os testes ao longo dos quatro anos e, somente no teste Equilíbrio à Retaguarda foi encontrada uma interação significativa entre tempo e sexo. A correlação de Pearson apresentou uma estabilidade moderada. No teste Equilíbrio à Retaguarda, em ambos os sexos, e Saltos Monopedais nos meninos não se verificou nenhum tracking no desempenho o que revela uma forte heterogeneidade no desenvolvimento da Coordenação Motora ao longo dos quatro anos. Tais resultados reafirmam o direito à diferença nos níveis de coordenação e apelam para o entendimento do seu significado em termos pedagógicos.